RESPONSIBILITY TO PROTECT IN SYRIAN CRISIS: WHAT CAN BE EXPECTED FROM THE MUSLIM COMMUNITY? - Zakiyah Zakiyah (Analisa: Journal of Social Science and Religion, 2019)
This article concerns on the notion of responsibility to protect (R2P) in Syrian war and what can be expected from the Muslim community. This theme is important to be discussed for the reasons that crisis in Syria has been occurred for almost nine years since it began in March 2011 and it has no end sign in the immediate time. In addition, it caused hundred thousand civilians dead, million people become displaced persons. In addition, the use of chemical weapons in the Syrian war was against the international laws. This paper was written based on the data that was collected using documentary study. Findings of this research reveals that the Syrian civil war had involved various parties including the government, insurgent groups, international fighters, and several countries like the US, Saudi Arabia, Turkey, Russia, some European countries, and other states. This made the situation very complex. The Muslim communities through international organization such as Organization for Islamic Cooperation (OIC) and the International Syria Support Group (ISSG) should actively participate in implementing the R2P which include protecting people, promoting human rights issues, and preventing further mass killing as well as military protection.